PEMBERIAN MANIPULASI MILLS PADA TERAPI ULTRASOUND (US) DAN TRANSCUTANEUS ELECTRICAL NERVE STIMULATION (TENS) DAPAT LEBIH MENURUNKAN INTENSITAS NYERI PADA TENNIS ELBOW TIPE II - Sulasih, Ni Made (Majalah Ilmiah Fisioterapi Indonesia, 2013)
Tennis elbow is a painful type II lateral epicondilus characterized by inflammation of the extensor carpi radialis brevis tendoperiosteal due to the use of the hand and wrist excessively, causing small tears in the extensor carpi radialis brevis tendoperiosteal. This study aimed to determine the additional Mill’s manipulation in the US and TENS therapy can further decrease pain in tennis elbow type II. The study was conducted with the design of pre-test and post-test control group, which found the number of samples for the control group with the intervention of the US and TENS as many as 14 people, and the treatment group by the US, TENS, and Mill’s manipulation as many as 14 people. From the results of hypothesis testing using two different test average is paired sample t-test in the control group obtained t value of 40.48 with a mean value of 49.93, p <0.05 (0.000) which means there significant difference between the average value of pain before and after intervention. While the treatment group obtained t value of 77.60, an average of 67.30, p <0.05 (0.000) which means there is a significant difference between the average value of pain before and after intervention. From the results of hypothesis testing using two different test average the independent sample t-test obtained value of p <0.05 (0.000), which means intervention in the treatment group (US, TENS, and Mill’s manipulation) was significantly more effective than interventions in the control group (US and TENS) in reducing pain in tennis elbow type II. It can be concluded: Giving Mill’s manipulation on US intervention and TENS can further decrease the intensity of pain in tennis elbow type II.
Keywords: Tennis elbow type II, pain, US, TENS, Mill’s manipulation.